2018
DOI: 10.1111/pce.13177
|View full text |Cite
|
Sign up to set email alerts
|

mQTL-seq and classical mapping implicates the role of an AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED (AHL ) family gene in Ascochyta blight resistance of chickpea

Abstract: Ascochyta blight (AB) caused by the fungal pathogen Ascochyta rabiei is a serious foliar disease of chickpea (Cicer arietinum L.). Despite many genetic studies on chickpea-Ascochyta interaction, genome-wide scan of chickpea for the identification of AB-associated quantitative trait loci (QTLs) and their gene(s) has not been accomplished. To elucidate narrow QTLs for AB resistance, here, we report the use of multiple QTL-sequencing approach on 2 sets of extreme AB phenotype bulks derived from Cicer intraspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 52 publications
(121 reference statements)
3
38
1
Order By: Relevance
“…This QTL region has been narrowed down to 4.3–4.5 Mb genomic region using NGS-based BSA sequencing. A candidate gene Ca-AKL18 (AT‐HOOK MOTIF CONTAINING NUCLEAR LOCALIZED 18) gene was identified within this region (Kumar et al 2018 ). The Ca-AKL18 showed structural variation in the promoter region and had higher expression under ascochyta blight infection in the moderately resistant parent FLIP84‐92C, suggesting that this gene is the most probable candidate involved in resistance to ascochyta blight in chickpea (Kumar et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This QTL region has been narrowed down to 4.3–4.5 Mb genomic region using NGS-based BSA sequencing. A candidate gene Ca-AKL18 (AT‐HOOK MOTIF CONTAINING NUCLEAR LOCALIZED 18) gene was identified within this region (Kumar et al 2018 ). The Ca-AKL18 showed structural variation in the promoter region and had higher expression under ascochyta blight infection in the moderately resistant parent FLIP84‐92C, suggesting that this gene is the most probable candidate involved in resistance to ascochyta blight in chickpea (Kumar et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A candidate gene Ca-AKL18 (AT‐HOOK MOTIF CONTAINING NUCLEAR LOCALIZED 18) gene was identified within this region (Kumar et al 2018 ). The Ca-AKL18 showed structural variation in the promoter region and had higher expression under ascochyta blight infection in the moderately resistant parent FLIP84‐92C, suggesting that this gene is the most probable candidate involved in resistance to ascochyta blight in chickpea (Kumar et al 2018 ). Although the QTL interval of qAB4.1 overlapped with the QTL interval of QTL AR1 , fine mapping of this region by Kumar et al ( 2018 ) and Madrid et al ( 2012 ) suggested that the qAB4.1 identified in cultivar Amit (genomic region 6.0–8.6 Mb) could be different than the fine-mapped QTL region of FLIP84-92C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the genetic studies of chickpea have focused on the identification of genetic regions using different methodologies associated to improving agronomic traits, such as increasing seed yield and the yield of components [95,96,97,98,99,100,101,102,103]. In addition, a genetic approach has been used to develop drought/heat tolerance [70,104,105,106,107,108], as well as disease resistance, for example, Ascochyta blight [109,110]. Solid and broad genetic studies on chickpeas are emerging and paving the way for breeding approaches targeting phenolic compounds in general [111,112,113].…”
Section: Geneticsmentioning
confidence: 99%
“…Das et al(Das et al, 2016) crossed a less pod number variety ILWC 46 with two more pod number varieties Pusa 1103 and Pusa 256 respectively to obtain the F2 population for mQTL-seq, and then narrowed the candidate region through taking the intersection of the two candidate intervals. Kumar et al (Kumar et al, 2018) identified three genes related to Ascochyta blight resistance of chickpea based on mQTL-seq technology. The application of QTL-seq to some large genome, such as barley, is challenging, so Hisano et al (Hisano et al, 2017)identified the monogenic Mendelian locus and associated QTLs using Exome QTL-seq.…”
mentioning
confidence: 99%